2022
DOI: 10.3847/1538-4357/ac4165
|View full text |Cite
|
Sign up to set email alerts
|

The Intrinsic Structure of Sagittarius A* at 1.3 cm and 7 mm

Abstract: Sagittarius A* (Sgr A*), the Galactic Center supermassive black hole (SMBH), is one of the best targets in which to resolve the innermost region of an SMBH with very long baseline interferometry (VLBI). In this study, we have carried out observations toward Sgr A* at 1.349 cm (22.223 GHz) and 6.950 mm (43.135 GHz) with the East Asian VLBI Network, as a part of the multiwavelength campaign of the Event Horizon Telescope (EHT) in 2017 April. To mitigate scattering effects, the physically motivated scattering ker… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 102 publications
3
24
3
Order By: Relevance
“…The substructure manifests in the visibility domain as "refractive noise," which is an additive complex noise component with broad correlation structure across baselines and time (Johnson & Narayan 2016). Using observations of Sgr A * from 1.3 mm to 30 cm, Johnson et al (2018) have shown that the combined image broadening and substructure strongly constrain the power spectrum of density fluctuations, which is consistent with later observations that occurred close to the 2017 EHT observations of Sgr A * described in this work (Sections 4.1.1 and 4.1.2) and in Issaoun et al (2019bIssaoun et al ( , 2021 and Cho et al (2022).…”
Section: Interstellar Scatteringsupporting
confidence: 84%
See 2 more Smart Citations
“…The substructure manifests in the visibility domain as "refractive noise," which is an additive complex noise component with broad correlation structure across baselines and time (Johnson & Narayan 2016). Using observations of Sgr A * from 1.3 mm to 30 cm, Johnson et al (2018) have shown that the combined image broadening and substructure strongly constrain the power spectrum of density fluctuations, which is consistent with later observations that occurred close to the 2017 EHT observations of Sgr A * described in this work (Sections 4.1.1 and 4.1.2) and in Issaoun et al (2019bIssaoun et al ( , 2021 and Cho et al (2022).…”
Section: Interstellar Scatteringsupporting
confidence: 84%
“…The measured flux densities from Sgr A * at these frequencies are 1.07 ± 0.11 Jy and 1.35 ± 0.14 Jy, respectively (Table 2). Two of the observations on 2017 April 3 and 4 are (quasi-)simultaneous with the Global 3 mm VLBI Array observations (Section 4.1.2), as well as the EHT sessions (Cho et al 2022). These measurements provide an estimated size and flux density of Sgr A * at 1.3 mm via extrapolation of power-law models (i.e., the intrinsic size scales with observing wavelength as a power law with an index of ∼1.2 ± 0.2).…”
Section: Multiwavelength Observing Campaignmentioning
confidence: 99%
See 1 more Smart Citation
“…According to their results, a clear difference in the core shift between the two scenarios is shown. Especially at a small inclination angle, as has been suggested in recent studies [20][21][22], the expected core shift at 22-43 GHz is 10 µas in the accretion disk model while it is 100 µas in the jet model. Our preliminary core-shift measurements with the Korean VLBI Network (KVN) and the Very Long Baseline Array (VLBA) at the same frequencies show ∼100 µas (I.…”
supporting
confidence: 61%
“…We find that F radio for Sgr A * is ∼0.1 mJy, which may be challenging to detect. VLBI images on Sgr A * are likely affected by the refractive scattering effect in the foreground plasma, which effectively adds 1-10 mJy noises to the data (Cho et al 2022). Brinkerink et al (2019) reported a possible blob-like feature in their 86 GHz VLBI Sgr A * image with a flux density of ∼10 mJy.…”
Section: Application To Sgr a *mentioning
confidence: 99%